Trabecular Bone Score and Bone Mineral Density in Postmenopausal Women with Morbid Obesity—A Clinical Paradox - Antresa Jose; Kripa Elizabeth Cherian; Munaf Babajan Nandyal; Stephen A. Jiwanmall; Dheeraj Kattula; Thomas V. Paul; Nitin Kapoor (Medical Sciences, 2021)
Obesity has long been considered to have a protective effect on bone, but specific complications in those with morbid obesity are known to have a detrimental impact on bone architecture. We aimed to study the bone microarchitecture (TBS—trabecular bone score) and bone mineral density (BMD) in postmenopausal women with morbid obesity compared to obese and non-obese age-matched women. Eighty-five consecutive postmenopausal women with morbid obesity (body mass index (BMI) ≥ 35 kg/m2) were enrolled and compared to age-matched obese (n = 80) and non-obese postmenopausal controls (n = 85). The BMD and TBS were assessed in all subjects using a Hologic-QDR 4500-W Discovery-A DXA scanner. The mean BMD (gm/cm2) at the femoral neck in women with morbid obesity was found to be significantly lower as compared to the age-matched postmenopausal obese controls (0.723 versus 0.762, p-value = 0.002). The BMD at the lumbar spine and hip showed similar trends but were not statistically significant. The bone microarchitecture was found to be significantly lower in those with morbid obesity (1.205) as compared to the other two groups (obesity 1.244; non-obese 1.228) (p < 0.013). Though obesity was associated with a better bone density and bone microarchitecture in postmenopausal women, a paradoxical lower value was seen in those with morbid obesity.